2009
DOI: 10.1093/jac/dkn543
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the pharmacodynamics of imipenem in patients with ventilator-associated pneumonia following administration by 2 or 0.5 h infusion

Abstract: The 2 h infusions of imipenem resulted in greater t > MICs than the 0.5 h infusion. For infections caused by pathogens with high MICs, a 2 h infusion of 1 g of imipenem every 6 h can provide plasma concentrations above the MIC of 4 mg/L for 60% of a 6 h interval.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 18 publications
1
21
1
Order By: Relevance
“…0.5-h versus 3-h infusions [19,20]. In contrast, the current results (Table 3) indicated that the effects of infusion time on PK-PD breakpoints depended on CL Cr , and a prolonged infusion did not improve the PK-PD breakpoints in typical patients with a CL Cr of 20 mL/min and 60 mL/min.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…0.5-h versus 3-h infusions [19,20]. In contrast, the current results (Table 3) indicated that the effects of infusion time on PK-PD breakpoints depended on CL Cr , and a prolonged infusion did not improve the PK-PD breakpoints in typical patients with a CL Cr of 20 mL/min and 60 mL/min.…”
Section: Discussioncontrasting
confidence: 83%
“…These inconsistent findings may be explained by the patient demographics. In the abovementioned studies [19,20], healthy subjects and patients with ventilator-associated pneumonia were recruited and their CL Cr was 91.1 ± 8.2 mL/min and ≥60 mL/min, whereas the patients enrolled in the current study had CL Cr ranging from 8.7 mL/min to 130 mL/min. Given that IPM is a time-dependent killing antibiotic Table 3 Pharmacokinetic-pharmacodynamic (PK-PD) breakpoints for the dosing regimens of imipenem (0.5-h and 1.5-h infusions) in patient populations with varying renal function as determined by creatinine clearance (CLCr).…”
Section: Discussionmentioning
confidence: 99%
“…Based upon our findings, an understanding of the enzymatic mechanism of resistance mediated by KPC, and the initial limited expression of KPC by many strains, resulting in MICs that are raised but still in the susceptible range, patients infected with KPC-producing K. pneumoniae are unlikely to respond to carbapenems, even if these antibiotics are dosed according to the level of susceptibility manifested by the pathogen and appropriate pharmacokinetic/pharmacodynamic targets are achieved (37,43). On the other hand, infections due to isolates with Omp loss and coproduction of ESBLs might be treatable with carbapenems if MICs are in the susceptible range based on pharmacokinetic/pharmacodynamic targets (17,18,21,23,(29)(30)(31)(32)38). Further studies are needed to define these relationships and to determine if there is a clinical need to differentiate between the KPC-Kp and ESBL/Omp groups.…”
Section: Discussionmentioning
confidence: 99%
“…The studies found that a 3-h infusion of meropenem gives greater values for T > MIC than a bolus injection [12,13]. Other studies have found that a 2-h infusion of imipenem and a 4-h infusion of doripenem provide greater values for T > MIC than a bolus injection [14][15][16]. We have therefore suggested that administration by prolonging intermittent infusion may offer the opportunity to increase the T > MIC within the limitations of stability at room temperature.…”
Section: Introductionmentioning
confidence: 88%